HACCP design in the production of rapet wangi Madura herbal medicine at PT. Firdaus Kurnia Indah - Dian Farida Asfan; Iffan Maflahah; Emi Normalina Omar; Debirotul Auliya (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
PT. Firdaus Kurnia Indah is one of the traditional herbal medicine industries in Bangkalan. One of the herbal medicine products with the highest demand is rapet wangi. News about traditional herbal medicine that is added with hazardous chemicals can cause complaints that are very detrimental to health. Therefore, it is necessary to carry out material inspection and monitoring of the process of making traditional herbal medicine that is free from the dangers of chemicals. The method for identifying hazards in the production process was by using the HACCP (Hazard Critical Control Point) method. The application of HACCP in the process of making herbal rapet wangi produces critical control points (CCP) in the drying process and the printing process. In herbal rapet wangi products, it can be seen that the critical control points (CCP) are in the drying process and the printing process. In the drying process where the risk of contamination of pathogenic microbes is very high. The risk of contamination of pathogenic microbes is very high because it is feared that the microbes will not die even though they have been heated. In the process of forming herbal medicine, there is a risk of cross-contamination from workers and equipment because when forming herbal medicine it is round, does not use gloves, and does not use hair coverings.